Computational and field test analysis of thermal comfort performance of user-controlled thermal chair in an open plan office - Shahzad, Sally; Hughes, Ben; Calautit, John Kaiser; Nasir, Diana S.N.M. (Elsevier, 2017)
In this study, a thermal chair prototype was developed that allowed personal control over the temperature settings of the back-rest and the seat. Limited research focuses on different methods to provide individual user control over the thermal environment. This is particularly difficult to achieve in an open plan office setting, where changing the temperature in one area directly influences the comfort and satisfaction of other occupants seated nearby. In this study, the application of the thermal chair was analysed using Computational Fluid Dynamics (CFD) and field-test analysis in an open plan office in Leeds, UK during winter. The results of the CFD model indicated an improvement in the local thermal comfort of the user. The CFD analysis provided detailed analysis of the thermal distribution around a siting manikin and was used to design and construct the thermal chair. The results of the field data survey indicated a great improvement in users' comfort (20%) and satisfaction (35%). This study concludes that local thermal control of the occupant improves their overall thermal comfort. It recommends further work to optimise the design of the thermal chair and to improve the modelling for better predictions.